Identifying the chloroperoxyl radical in acidified sodium chlorite solution. - Hiroyuki Kawata; Masahiro Kohno; Kohei Nukina; Isanori Horiuchi; Hisataka Goda; Tomomi Kuwahara; Kosei Yoshimori; Akimitsu Miyaji; Toshiaki Kamachi; Toshikazu Yoshikawa (PLoS ONE)
The present study identified the active radical species in acidic sodium chlorite and investigated the feasibility of quantifying these species with the diethylphenylenediamine (DPD) method. Electron spin resonance (ESR) spectroscopy was used to identify the active species generated in solutions containing sodium chlorite (NaClO2). The ESR signal was directly observed in an acidified sodium chlorite (ASC) aqueous solution at room temperature. This ESR signal was very long-lived, indicating that the radical was thermodynamically stable. The ESR parameters of this signal did not coincide with previously reported values of the chlorine radical (Cl●) or chlorine dioxide radical (O = Cl●-O and O = Cl-O●). We refer to this signal as being from the chloroperoxyl radical (Cl-O-O●). Quantum chemical calculations revealed that the optimal structure of the chloroperoxyl radical is much more thermodynamically stable than that of the chlorine dioxide radical. The UV-visible spectrum of the chloroperoxyl radical showed maximum absorbance at 354 nm. This absorbance had a linear relationship with the chloroperoxyl radical ESR signal intensity. Quantifying the free chlorine concentration by the DPD method also revealed a linear relationship with the maximum absorbance at 354 nm, which in turn showed a linear relationship with the chloroperoxyl radical ESR signal intensity. These linear relationships suggest that the DPD method can quantify chloroperoxyl radicals, which this study considers to be the active species in ASC aqueous solution.